Human sacrifice and value
1 online resource
Keywords: "This volume explores concepts of human sacrifice, focusing on its value - or multiplicity of values - in relative cultural and temporal terms, whether sacrifice is expressed in actual killings, in ideas revolving around ritualized, sanctioned, or sanctified violence or loss, or in transformed and (often sublimated) undertakings"--